Biosorprption of Anionic Dye Bezaktiv Yellow HE-4G on Mixture of Olive Stone and Date Pits in Packed Bed Column - Babaci, H.; Aksas, H.; Louhab, K. (Asian Journal of Chemistry, 2015)
In this paper, the adsorption of anionic dye Bezaktiv Yellow HE-4G onto mixture biosorbent, olive stones and date pits was investigated in packed bed column. The effect of operational parameter such as initial dye concentration, flow rate and height bed was evaluated. Thomas model was used to describe the adsorption data. Adjunction date pits to the mixture increase the per cent of dye adsorbent it is about 19 to 43.23 % when the date pits was added to the mixture between 12 to 15 %. The results indicated that the mixture of date pits and olive stone could be used as an adsorbent for textile waste water treatment without high cost.